A Theory of Job Shopping - Johnson, William R. (Quarterly Journal of Economics, 1978)
I. Introduction, 261.—II. The basic model—risk neutrality, 262.—III. Mobility cost, 268.—IV. Education, 270.—V. Extensions of the basic model, 272.—VI. Empirical applications, 274.